POLIGAMI PERSPEKTIF MUHAMMAD ABDUH DAN MUHAMMAD SYAHRUR - Nur Khosiah; Reza Hilmy Luayyin; David Prabowo (LPPM STAI Muhammadiyah Probolinggo, 2021)
This research is library research that uses qualitative descriptive methods. This study reviewed Muhammad Abduh and Muhammad Syarhrur thought. Both of them contemporary scholars whose work is well known to the world. The Researcher is interest in studying the thinking of their both about polygamy because there are significant has similarities and differences from the perspective in interpreting polygamy verses in the Qur'an, surah An-Nisa verses 3 and 129. Both of them have different conditions when it comes to polygamy. Abduh banned polygamy on the grounds of justice and Syahrur vowed in terms of quality. But in terms of quantity there is no difference between them. The result of this study showed that Muhammad Abduh allowed polygamy by using conditions in an emergency. The conditions that allow among the first wife there are indications of barrenness, no doubt in doing justice, or no fear of a dispute after marriage. Abduh did not think too much in terms of the quality of the wife who would be polygamy. While Syahrur allows polygamy with qualification conditions in terms of quality where the status of widows of wives who have children applies to the second, third or fourth wives. There is no difference between the two in terms of quantity.